Notes on the lizard community at a restinga protected area in the state of Rio de Janeiro, southeastern Brazil - Murta Fonseca, Roberta A.; Martins, Angele R.; Fratani, Jéssica; Mattedi, Camila; Pontes, Rafael; Brandão, Amaurício L. R.; Pinto, Roberta R. (Herpetologia Brasileira, 2026)
Restingas are ecosystems of complex types of coastal vegetation inserted in the Atlantic Forest biome which have been subjected to intense human impact and degradation in the last decades. Studies on the ecological factors that shape lizard communities remain as a remarkable initiative of better understanding such complex types of habitats. In this study we analyze the natural history aspects of the lizard community in four areas within Parque Estadual da Costa do Sol, Rio de Janeiro, Brazil. We gathered data on the composition, distribution of species, and microhabitat usage during a short-term fieldwork. For such purposes, we conducted four quarterly field expeditions from May 2012 to January 2013, and data was gathered through the use of time constrained active search. Seven species of lizards were recorded in the area, with a relative abundance of 1.45 individuals/hour. Lizard species abundance was higher in Dunas and Massambaba areas, compared to Área de Proteção Ambiental Pau Brasil (A.P.A. Pau Brasil). Species richness was equal for both rainy and dry seasons. Lizard microhabitat occupancy was categorized into seven ranks that varied between species in each of the four studied areas. The lizard community found within the studied areas is similar to those from previous studies carried out in restinga habitats and dry forests along the Brazilian coast. Our results highlight the importance on the conservation of such areas in order to ensure the viability of lizard populations found therein.